2021
DOI: 10.3389/fsoc.2021.618107
|View full text |Cite
|
Sign up to set email alerts
|

Health Sciences Interprofessional Collaborative: A Perspective on Migration, COVID-19, and the Impact on Indigenous Communities

Abstract: At the United States-Mexico border, the impacts of immigration policy are dynamic with political, humanitarian, and health outcomes. This article highlights the experiences at the Casa Alitas migrant shelter in Tucson, Arizona. Casa Alitas aims to meet the needs of the im/migrants it serves, including the unique needs of indigenous asylum-seekers from Central America. We highlight the importance of community-based humanitarian response to support asylum-seekers in a way that acknowledges our shared humanity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The geopolitical reality also creates crisis points for residents, such as the constant influx of asylum seekers and the closing of the border during the peak of the COVID-19 pandemic. Border communities consistently respond to these crises by creating humanitarian aid infrastructure powered by volunteers and community organizations [36], perhaps further evidence of their affiliation to a border identity with distinct personal and moral obligations.…”
Section: Discussionmentioning
confidence: 96%
“…The geopolitical reality also creates crisis points for residents, such as the constant influx of asylum seekers and the closing of the border during the peak of the COVID-19 pandemic. Border communities consistently respond to these crises by creating humanitarian aid infrastructure powered by volunteers and community organizations [36], perhaps further evidence of their affiliation to a border identity with distinct personal and moral obligations.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, these age-based findings were obtained after controlling for education, occupation, and income, which are strong determinants of remote work capabilities (Bartik et al 2020; Brynjolfsson et al 2020; Dingel and Neiman 2020; Kavanagh et al 2021). More so than in younger adulthood, advancing age in later life implies greater vulnerability to the consequences of COVID-19 infection (Landau et al 2021; Wolf et al 2020), a fact that obtains throughout the socioeconomic spectrum. Accordingly, in concert with the HBM, older workers within later life might show intensified remote work negotiations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown individual-level age and health to predict pandemic-era remote work, since they affect risk of serious health complications and mortality concomitant to COVID-19 infection (Landau et al 2021; Wolf et al 2020). Accordingly, having an underlying respiratory condition predicted working remotely (Camacho-Rivera, Islam, and Vidot 2020).…”
Section: Previous Research Conceptual and Theoretical Frameworkmentioning
confidence: 99%
“…According to Kladzyk et al, indigenous language speakers face greater risks while in Mexico traveling to the United States. They are more likely to suffer from persecution before coming to the United States (Landau, et al, 2021). In a newspaper article, Kladzyk et al reported indigenous language speakers in shelters in northern Mexico face language barriers, and that "significant problems await" in immigration court.…”
Section: Indigenous Language Speakers Interacting In Immigration Courtmentioning
confidence: 99%